Effects of a stress management intervention on salivary cortisol during competition of western performance equestrians - A. Baxter; J.L. Zoller; C.J. Huseman; J. Ripley; L. Colvin; P. Linne (Journal of Equine Veterinary Science, 2025)

Effects of snake fungal disease (ophidiomycosis) on the skin microbiome across two major experimental scales - Alexander S. Romer; Matthew Grisnik; Jason W. Dallas; William Sutton; Christopher M. Murray; Rebecca H. Hardman; Tom Blanchard; Ryan J. Hanscom; Rulon W. Clark; Cody Godwin; N. Reed Alexander; Kylie C. Moe; et al. (Conservation Biology, 2025)
Emerging infectious diseases are increasingly recognized as a significant threat to global biodiversity conservation. Elucidating the relationship between pathogens and the host microbiome could lead to novel approaches for mitigating disease impacts. Pathogens can alter the host microbiome by inducing dysbiosis, an ecological state characterized by a reduction in bacterial alpha diversity, an increase in pathobionts, or a shift in beta diversity. We used the snake fungal disease (SFD; ophidiomycosis), system to examine how an emerging pathogen may induce dysbiosis across two experimental scales. We used quantitative polymerase chain reaction, bacterial amplicon sequencing, and a deep learning neural network to characterize the skin microbiome of free‐ranging snakes across a broad phylogenetic and spatial extent. Habitat suitability models were used to find variables associated with fungal presence on the landscape. We also conducted a laboratory study of northern watersnakes to examine temporal changes in the skin microbiome following inoculation with Ophidiomyces ophidiicola . Patterns characteristic of dysbiosis were found at both scales, as were nonlinear changes in alpha and alterations in beta diversity, although structural‐level and dispersion changes differed between field and laboratory contexts. The neural network was far more accurate (99.8% positive predictive value [PPV]) in predicting disease state than other analytic techniques (36.4% PPV). The genus Pseudomonas was characteristic of disease‐negative microbiomes, whereas, positive snakes were characterized by the pathobionts Chryseobacterium , Paracoccus , and Sphingobacterium . Geographic regions suitable for O. ophidiicola had high pathogen loads (>0.66 maximum sensitivity + specificity). We found that pathogen‐induced dysbiosis of the microbiome followed predictable trends, that disease state could be classified with neural network analyses, and that habitat suitability models predicted habitat for the SFD pathogen.

A Meta-Analysis of the Genome-Wide Association Studies on Two Genetically Correlated Phenotypes Suggests Four New Risk Loci for Headaches - Weihua Meng; Parminder S. Reel; Charvi Nangia; Aravind Lathika Rajendrakumar; Harry L. Hebert; Qian Guo; Mark J. Adams; Hua Zheng; Zen Haut Lu; Debashree Ray; Lesley A. Colvin; Colin N. A. Palmer; et al. (Phenomics, 2023)
Headache is one of the commonest complaints that doctors need to address in clinical settings. The genetic mechanisms of different types of headache are not well understood while it has been suggested that self-reported headache and self-reported migraine were genetically correlated. In this study, we performed a meta-analysis of genome-wide association studies (GWAS) on the self-reported headache phenotype from the UK Biobank and the self-reported migraine phenotype from the 23andMe using the Unified Score-based Association Test (metaUSAT) software for genetically correlated phenotypes ( N = 397,385). We identified 38 loci for headaches, of which 34 loci have been reported before and four loci were newly suggested. The LDL receptor related protein 1 ( LRP1 )— Signal Transducer and Activator of Transcription 6 ( STAT6 )— S hort chain D ehydrogenase / R eductase family 9C member 7 ( SDR9C7 ) region in chromosome 12 was the most significantly associated locus with a leading p value of 1.24 × 10 –62 of rs11172113. The One Cut homeobox 2 ( ONECUT2 ) gene locus in chromosome 18 was the strongest signal among the four new loci with a p value of 1.29 × 10 –9 of rs673939. Our study demonstrated that the genetically correlated phenotypes of self-reported headache and self-reported migraine can be meta-analysed together in theory and in practice to boost study power to identify more variants for headaches. This study has paved way for a large GWAS meta-analysis involving cohorts of different while genetically correlated headache phenotypes.

Electronic cigarette vaping with aged coils causes acute lung injury in mice - Shunsaku Goto; Robert M. H. Grange; Riccardo Pinciroli; Ivy A. Rosales; Rebecca Li; Sophie L. Boerboom; Katrina F. Ostrom; Eizo Marutani; Hatus V. Wanderley; Aranya Bagchi; Robert B. Colvin; Lorenzo Berra; et al. (Archives of Toxicology, 2022)

Growth, reproduction, and age at maturity of Lessa’s butterfly ray Gymnura lessae in the northern Gulf of Mexico - Matthew B. Jargowsky; Bryan L. Huerta-Beltrán; Matthew J. Ajemian; Michael E. Colvin; J. Marcus Drymon (Environmental Biology of Fishes, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A newly recorded Rickettsia of the Torix group is a recent intruder and an endosymbiont in the whitefly Bemisia tabaci - Hua‐Ling Wang; Teng Lei; Xiao‐Wei Wang; M. N. Maruthi; Dan‐Tong Zhu; Stephen L. Cameron; Qiong Rao; Hong‐Wei Shan; John Colvin; Yin‐Quan Liu; Shu‐Sheng Liu (Environmental Microbiology, 2020)
Summary The bacterium Rickettsia is found widely in phytophagous insects and often exerts profound effects on the phenotype and fitness of its hosts. Here, we decrypt a new, independent, phylogenetically ancient Torix Rickettsia endosymbiont found constantly in a laboratory line of an economically important insect Asia II 7, a putative species of the Bemisia tabaci whitefly complex (Hemiptera: Aleyrodidae), and occasionally in field whitefly populations. This new Rickettsia distributes throughout the body of its whitefly host. Genetically, compared to Rickettsia_ bellii_MEAM1 found earlier in whiteflies, the new Rickettsia species has more gene families and pathways, which may be important factors in shaping specific symbiotic relationships. We propose the name ‘ Candidatus Rickettsia_Torix_ Bemisia_tabaci (RiTBt)’ for this new endosymbiont associated with whiteflies. Comparative genomic analyses indicate that RiTBi may be a relatively recent intruder in whiteflies given its low abundance in the field and relatively larger genome compared to Rickettsia _bellii_MEAM1.

Estimates of environmental loading from copper alloy materials - Patrick J. Earley; Brandon L. Swope; Marienne A. Colvin; Gunther Rosen; Pei-Fang Wang; Jessica Carilli; Ignacio Rivera-Duarte (Biofouling, 2020)

Boundary spanning at the science–policy interface: the practitioners’ perspectives - A. T. Bednarek; C. Wyborn; C. Cvitanovic; R. Meyer; R. M. Colvin; P. F. E. Addison; S. L. Close; K. Curran; M. Farooque; E. Goldman; D. Hart; H. Mannix; et al. (Sustainability Science, 2018)

Dietary plasticity in a nutrient-rich system does not influence brown bear (Ursus arctos) body condition or denning - Lindsey S. Mangipane; Jerrold L. Belant; Diana J. R. Lafferty; David D. Gustine; Tim L. Hiller; Michael E. Colvin; Buck A. Mangipane; Grant V. Hilderbrand (Polar Biology, 2018)

Nickel and Copper Toxicity to Embryos of the Long-Spined Sea Urchin, Diadema savignyi - G. Rosen; I. Rivera-Duarte; M. A. Colvin; R. E. Dolecal; L. J. Raymundo; P. J. Earley (Bulletin of Environmental Contamination and Toxicology, 2015)

Pharmacological characterisation of ligand- and voltage-gated ion channels expressed in human iPSC-derived forebrain neurons - Jeffrey L. Dage; Ellen M. Colvin; Antoine Fouillet; Emily Langron; William C. Roell; Jingling Li; Sachin X. Mathur; Adrian J. Mogg; Matthew G. Schmitt; Christian C. Felder; Kalpana M. Merchant; John Isaac; et al. (Psychopharmacology, 2014)

The bacterial communities in plant phloem‐sap‐feeding insects - Xiangfeng Jing; Adam C‐N Wong; John M. Chaston; John Colvin; Cindy L. McKenzie; Angela E. Douglas (Molecular Ecology, 2014)
The resident microbiota of animals represents an important contribution to the global microbial diversity, but it is poorly known in many animals. This study investigated the bacterial diversity in plant phloem‐sap‐feeding whiteflies, aphids and psyllids by pyrosequencing bacterial 16 S rRNA gene amplicons. After correction for sequencing error, just 3–7 bacterial operational taxonomic units were recovered from each insect sample sequenced to sufficient depth for saturation of rarefaction curves. Most samples were dominated by primary and secondary symbionts, which are localized to insect cells or the body cavity, indicative of a dearth of bacterial colonists of the gut lumen. Diversity indices of the bacterial communities ( S hannon's index: 0.40–1.46, S impson's index: 0.15–0.74) did not differ significantly between laboratory and field samples of the phloem‐feeding insects, but were significantly lower than in drosophilid flies quantified by the same methods. Both the low bacterial content of the phloem sap diet and biological processes in the insect may contribute to the apparently low bacterial diversity in these phloem‐feeding insects.

Pollution magnet: nano-magnetite for arsenic removal from drinking water - Cafer T. Yavuz; J. T. Mayo; Carmen Suchecki; Jennifer Wang; Adam Z. Ellsworth; Helen D’Couto; Elizabeth Quevedo; Arjun Prakash; Laura Gonzalez; Christina Nguyen; Christopher Kelty; Vicki L. Colvin (Environmental Geochemistry and Health, 2010)

Relationship Between Six Years of Corn Yields and Terrain Attributes - Thomas C. Kaspar; Thomas S. Colvin; Daniel B. Jaynes; Douglas L. Karlen; David E. James; David W. Meek; Daniel Pulido; Howard Butler (Precision Agriculture, 2003)